Pengembangan Perangkat Lunak Pembelajaran Jaringan Komputer Untuk Siswa Kelas Xi Berbasis Android - Sunarko, Abdul Rohmaan; , Drs. Sudjalwo, M.Kom (2016)
In this day, studying with a textbook at school are common, but the learning metthod like that still constrained by distance, we have to bring the textbook wile learning and about time problem. But with the advancement of information and communication technologies has been growing rapidly, today is no longer a problem. Information and communication technology is more advanced at this time , present us a smartphone with an operating system. The operating system is Android. And tha so, We made a textbook application of Computer Networks in the Android-based smart phone that has high portability and can help students to learn wherever and whenever they want, because now these subjects is already in the grip of their smart phones. This application is also expected to raise the value of academic subjects of Computer Network for students itself. To make this application, we using Eclipse software to create and edit script code and Corel Draw X5 for image processing. The application development was built through following steps: data collection, system designing, system development, testing and implement. The result of this research resulted the mobile application Android-based smartphones can be used for learning subjects Computer Network. This application has some fitures such Subjects menu, exercises menu and galleries menu.